Microsilica influence on the phase consTITUTION and properties of spinel-forming composition - Пісчанська, Вікторія Вікторівна; Войтюк, Ганна Сергіївна; Пітак, Ярослав Миколайович (Eastern-European Journal of Enterprise Technologies, 2015)
Experience in using low cement alumina-magnesia castables, containing spinel-forming reagents, in monolithic ladle linings identified their significant advantages in terms of thermomechanical properties, corrosion resistance and slag resistance. A particular feature of these castables is the synthesis of «in situ» magnesium aluminate spinel at high operating temperatures, which provides increased operational lifetime of the lining. The microsilica influence on the phase constitution of the composite mixture, containing calcium aluminate cement and spinel-forming reagents - calcined alumina and sintered periclase after firing at 17000C was investigated in the paper. It was found that as a result of the interaction of cement calcium aluminates with microsilica, fusible compounds - anorthite and helenite that, at increased microsilica content, impair physical and technical properties of the composite are formed. It was determined that the ratio of spinel-forming reagents and content of the silica-containing material in a matrix component of alumina-magnesia castables is a more important factor of the synthesis of high-melting-point crystalline phases than the microsilica content. Directed regulation of the phase constitution of the matrix component of alumina-magnesia castables by adjusting the grain-size composition of spinel-forming reagents and their optimal ratio will ensure achieving a set of the given physical and technical characteristics of concrete and increasing the operational lifetime of monolithic ladle linings.